2001
DOI: 10.1074/jbc.m005685200
|View full text |Cite
|
Sign up to set email alerts
|

3-Phosphoinositide-dependent Protein Kinase 1, an Akt1 Kinase, Is Involved in Dephosphorylation of Thr-308 of Akt1 in Chinese Hamster Ovary Cells

Abstract: To investigate the role of 3-phosphoinositide-dependent protein kinase 1 (PDK1) in the Akt1 phosphorylation state, wild-type (wt) PDK1 and its kinase dead (kd) mutant were expressed using an adenovirus gene transduction system in Chinese hamster ovary cells stably expressing insulin receptor. Immunoblotting using antiphosphorylated Akt1 antibody revealed Thr-308 already to be maximally phosphorylated at 1 min but completely dephosphorylated at 5 min, with insulin stimulation, whereas insulin-induced Akt1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 45 publications
7
38
1
Order By: Relevance
“…However, it could also reflect differences in the activities of, or accessibilities by various phosphatases to the different activation loops. Surprisingly little is known about phosphatases which act on the activation loop residues of AGC kinases, with limited evidence implicating protein phosphatase 2A (PP2A) for PKB/Akt and PKC isoforms [40,41]. Given the large disparity seen here for dephosphorylation of different activation loop residues, further work in this area is warranted.…”
Section: Discussionmentioning
confidence: 94%
“…However, it could also reflect differences in the activities of, or accessibilities by various phosphatases to the different activation loops. Surprisingly little is known about phosphatases which act on the activation loop residues of AGC kinases, with limited evidence implicating protein phosphatase 2A (PP2A) for PKB/Akt and PKC isoforms [40,41]. Given the large disparity seen here for dephosphorylation of different activation loop residues, further work in this area is warranted.…”
Section: Discussionmentioning
confidence: 94%
“…We do not see any evidence of differential S473 versus T308 early phase phosphorylation, but this may be due to a lack in temporal resolution at early times in our experiment. Although the phosphorylation of T308 and S473 is expected to be tightly coupled, several studies have shown that the dephosphorylation of these two sites is uncoupled [10,11]. In particular, prior studies using the shellfish toxin okadaic acid suggest that phosphatase activity at the T308 site is not connected to dephosphorylation at the S473 site, with further work suggesting that the phosphatase PP2A is responsible for T308 dephosphorylation [10,11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the phosphorylation of T308 and S473 is expected to be tightly coupled, several studies have shown that the dephosphorylation of these two sites is uncoupled [10,11]. In particular, prior studies using the shellfish toxin okadaic acid suggest that phosphatase activity at the T308 site is not connected to dephosphorylation at the S473 site, with further work suggesting that the phosphatase PP2A is responsible for T308 dephosphorylation [10,11,17]. Gao et al recently showed that a novel phosphatase, PHLPP, is responsible for dephosphorylating the S473 site [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations